EFFECTIVELY HUITT LEARNING MODEL WITH QUESTION MEDIA CARD AND PQ4R LEARNING MODEL WITH FLIP BOX MAKER MEDIA IN RESULT OF BEKL LOGIC MATHEMATIC IN STUDENT CLASS X PUBLIC SENIOR HIGH SCHOLL 1 SEMARANG - Suparman Suparman Suparman; Sri Kadarwati; Nurmawati Nurmawati (Program Studi Pendidikan Sejarah - Universitas Samudra, 2015)
Mathematic always consider difficult subject from elementary, junior, until senior high school students, this happens because mathematic consider connected with abstract objects, because of that mathematics teacher should have great understanding within subject, able to choose great strategy learning, also able to use learning model that can improve student motivation in learning and student will become active in learning. With all those considerations can be used to improve students learning progress. In fact, show that learning progress mathematic on Logic material class X in public senior high school I Semarang teacher still dominated. Students look passive – only receive material that teacher gave. Also, the teacher not using learning media, not yet used strategy and method which can stimulate students then understanding of the material still below expectation. To handle passivity within lack of understanding students in logic material class X Huitt learning model with Question Card media and PQ4R learning model with Flip Box Maker Media. Through this two learning model will be supervised a student's effective so can improve the result of students learning. This research used experimental kinds with two classes as an experiment and one class as control class, as populated in this research is entire students of class X which consider from eight classes, and continue randomly chosen, three classes. One class as an experiment I which applied Huitt learning model with Question Card Media, another class as experiment class II which applied PQ4R learning Flip Box Maker media, the rest of the class as a control class. Data processing has used a statistic (Normality test, Homogenates test, and ANOVA test). Point of this research is to: 1) to get that there are differences in mathematic learning which students applied Huitt learning model with Question card media, PQ4R learning model with Flip Box Maker Media, and Ekospositori learning model on material discussion mathematic logic curriculum 2014/2015. From this research shows there is differences students result in learning mathematic which applied Huitt learning model with question card media, PQ4R learning media with Flip Box Maker media, and Ekospositori learning model, learning more effective and there are differences in students learning Mathematic Logic curriculum 2014/2015.